Impacts of marketing strategy and social media activity on the profitability of online wine shops: The case of Hungary - Jeremiás Máté Balogh; Tamás Mizik (Economies, 2022)
Today, the wine business can benefit significantly from the advantages of online sales and the use of social media. However, while the online wine business is growing and the number of online buyers is increasing in Hungary, the impact of online marketing and social media use on their profitability is understudied. The research aims to apply qualitative data collection techniques such as web-content analysis to capture the elements of online marketing as an engine of stimulating profitability. For this reason, the top 12 Hungarian online wine shops were analyzed. The results revealed that the Hungarian online wine business is highly concentrated, the five main players (Vinotrade, Törley, Grape-Vine, Borháló, and Bortársaság) attract most buyers and account for the highest profit rate. Using online marketing channels and social media, wine shops can positively influence their profitability. In addition to the classic online marketing tools of the Internet (blogs, newsletters), social networks (Facebook, Instagram, Twitter, and Pinterest) of wine shops become highly relevant to boost wine sales. However, offline platforms (wine tastings, dinners, picnics) are still used by Hungarian online wine business. Online shops with strong retail and wholesale connections were better off, and the retail pillar becomes more important.
Keywords: 330; Hungary; online marketing; profitability; social media; wine business